Therapeutic Effect of Crocin on the NASH Model by Targeting the Fas Receptor Signaling Pathway - Mard, Seyyed Ali; Savari, Feryal; Rezaie, Anahita; Khosravi, Maryam (Turkish Journal of Gastroenterology, 2022)
Background: The role of hepatocyte apoptosis and inflammation has been implicated in the progression of nonalcoholic steatohepatitis (NASH). Overproduction of reactive oxygen species (ROS) appears to accelerate these pathways through the activation of Fas receptor signaling. Therefore, we explored the hepatoprotective effects of crocin as a strong free radical scavenger against oxidative damages leading to NASH development.Methods: Thirty-two male mice were randomly divided into control, NASH, NASH + crocin, and crocin groups. They received an intraperi- toneal injection of crocin twice a week, for 3 weeks. For NASH model induction, the animals were fed with a Western diet and exposed to cigarette smoke for 8 weeks. At the end of the experiment, liver histology, biochemical, and biomolecular analyses were done to evaluate the antioxidant, anti-inflammatory, and anti-apoptotic activities of crocin in the NASH model.Results: Evaluation of the features of the NASH model revealed steatosis, inflammatory infiltrate, and ballooning degeneration. Metabolic dysfunction was associated with elevated serum levels of the lipid profile and decreased hepatic liver enzymes. The increased content of malondialdehyde (MDA) and reduced antioxidant activities confirmed hepatotoxicity induction. There was a significant increase in expression level of Fas, caspase 3, and NF-κB genes that was also associated with elevation in hepatic TNF-α content. Moreover, expression the of Fas receptor protein was significantly detected on the hepatocyte membrane.Treatment with crocin effectively improved NASH-related parameters, and the histopathological findings were also parallel with the resulting changes.Conclusion: Crocin can be introduced as a candidate hepatoprotective agent against NASH by virtue of its anti-inflammatory, antioxi- dant, and anti-apoptotic properties, possibly through regulation of the Fas death receptor pathway.